Unruptured cerebral aneurysm clipping: association of combined open and endovascular expertise with outcomes. (18th September 2015) - Bekelis, Kimon; Gottlieb, Dan; Bovis, George; Su, Yin; Tjoumakaris, Stavropoula; Jabbour, Pascal; MacKenzie, Todd A
Abstract : Background: It is often questioned if one physician can conduct both open and endovascular techniques successfully and safely. Objective: To investigate the association of combined open and endovascular expertise with the outcomes of unruptured cerebral aneurysm clipping. Methods: We performed a cohort study of 100% of Medicare fee-for-service claims data for elderly patients who underwent surgical clipping for unruptured cerebral aneurysms between 2007 and 2012. To control for confounding we used propensity score conditioning, and controlled for clustering at the physician level. Results: During the study, 3247 patients underwent clipping for unruptured cerebral aneurysms, and met the inclusion criteria. Of these, 766 (23.6%) underwent treatment by hybrid neurosurgeons, and 2481 (76.4%) by proceduralists, who performed only clipping. Multivariable regression analysis with propensity score adjustment demonstrated a lack of association of combined practice with 1-year postoperative mortality (OR=0.81; 95% CI 0.51 to 1.28), discharge to rehabilitation (OR=0.95; 95% CI 0.72 to 1.25), length of stay (adjusted difference 0.85 days; 95% CI −0.31 to 2.00), or 30-day readmission rate (OR=1.05; 95% CI 0.80 to 1.39). Higher procedural volume was independently associated with improved outcomes. Conclusions: In a cohort of Medicare patients with unruptured aneurysms, we did not demonstrate a difference in mortality, discharge to rehabilitation, or readmission rate between hybrid neurosurgeons and surgeons performing only clipping.